2022
DOI: 10.3390/foods11131920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Six Lactic Acid Bacteria Strains on Physicochemical Characteristics, Antioxidant Activities and Sensory Properties of Fermented Orange Juices

Abstract: Six lactic acid bacteria strains were used to study the effects on physicochemical characteristics, antioxidant activities and sensory properties of fermented orange juices. All strains exhibited good growth in orange juice. Of these fermentations, some bioactive compositions (e.g., vitamin C, shikimic acid) and aroma-active compounds (e.g., linalool, 3-carene, ethyl 3-hydroxyhexanoate, etc.) significantly increased in Lactiplantibacillus plantarum and Lactobacillus acidophilus samples. DPPH free radical scave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 47 publications
8
20
0
Order By: Relevance
“…The lactic acid fermentation seemed to significatively increase alcohol concentration in the FR samples, being 1-decanol (sweet fat-like odour) the one with the higher concentration. Similar results were reported in fermented orange juice by Quan et al (2022) and in orange peels by Deba-Rementeria et al (2021); these authors attributed the increase of alcohols to the degradation of glucose and the catabolism of amino acids due to the microbial activity. Besides these slight differences in the volatile composition with the SUC sample, the FR sample was similarly liked.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…The lactic acid fermentation seemed to significatively increase alcohol concentration in the FR samples, being 1-decanol (sweet fat-like odour) the one with the higher concentration. Similar results were reported in fermented orange juice by Quan et al (2022) and in orange peels by Deba-Rementeria et al (2021); these authors attributed the increase of alcohols to the degradation of glucose and the catabolism of amino acids due to the microbial activity. Besides these slight differences in the volatile composition with the SUC sample, the FR sample was similarly liked.…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were reported in fermented orange juice by Quan et al . (2022) and in orange peels by Deba‐Rementeria et al . (2021); these authors attributed the increase of alcohols to the degradation of glucose and the catabolism of amino acids due to the microbial activity.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The pharmacological activities of many bioactive substances are enhanced under the action of probiotic biotransformation (17). Fuente et al (15) studied the influence of lactic acid bacteria on the physicochemical indexes of orange juice and found that fermented orange juice had higher total polyphenol content and antioxidant capacity (18). Probiotic fermentation can produce a variety of antagonistic metabolites, such as antifungal compounds and bacteriocins, which can inhibit the growth of harmful microorganisms during storage (19).…”
Section: Introductionmentioning
confidence: 99%